Réponses

Meilleure réponse !
2014-04-05T18:45:31+02:00
Bonsoir
19)
(x-4)² = x² - 8x +16        (x-5)² = x² - 10x +25          (5x-1)² = 25x² - 10x +1
(10 -3x)² = 100 - 60x +9x²

N°20
(7-x)(7+x) = 49 - x²
(1 -y)(1+y) = 1 -y²
(1 -3x)( 1 +3x) = 1 -9x²
(5b +2)(5b -2) = 25b² +4

21)
(1 +x)² = 1 + 2x +x²
(1 -b)² = 1 - 2b +b²
(2x +6)² = 4x² + 24x +36
(a+10)(a-10) = a² -100

22)
(10 -x)² = 100 - 20x + x²
(x+9)(x-9) = x² -81
(10 +x) ²= 100 + 20x +x²
(7 +8x)² = 49 + 112x + 64x²

23)
(3 -4x)² = 9 - 24x + 16x²
(10 +9x)(10 -9x ) = 100 - 81x²
(3y +6)² = 9y² + 36y +36
(8x -6y)(8x +6y) = 64x² - 36y²

24)
(3 +2x)² = 9 + 12x +4x²
(3 +2x)(3 -2x) =  9 - 4x²
(3 -2x)² = 9 - 12x +4x²
(2x-3)(2x+3) = 4x² -9

25) .
(x+2)² +9 = (x+2 +3)(x+2 -3) = (x+5)(x -1)
(2x +1)² - x +3 = 4x² +4x +1 -x +3 = 4x² +3x +4
(3x-2)² - 5(x +3) = 9x² - 12x +4 - 5x -15 = 9x² -17x - 11
(x+5)² + 3(x+6) = x² + 10x +25 +36x +18 = x² + 46x + 43

ouf !